2016
DOI: 10.1007/s12639-016-0819-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapecutic efficacy of the leaf extract of Croton joufra Roxb. against experimental cestodiasis in rats

Abstract: The leaves of have been used as a traditional medicine in Assam (Northeast India) to treat the intestinal helminthic infections. The aim of this study was to establish the in vitro and in vivo anthelmintic efficacy of the leaf extract of this plant on, a zoonotic tapeworm. The plant extract was also screened for its chemical constituents. The in vitro anthelmintic efficacy of the plant was evaluated by physical motility test on adult cestodes, following their exposure to 10, 20, 30 mg/ml concentrations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…To date, only a few studies on anthelmintic potentials of medicinal plants have backed their in vitro assays with in vivo studies. For example, Gogoi and Yadav (2016) and Gogoi and Yadav (2017) have supplemented their in vitro anthelmintic studies of plants with in vivo studies, using H. diminuta-rat and S. obvelata-mice models [18,30]. The findings are in agreement with that of Gogoi and Yadav (2016), who in their in vitro and in vivo efficacy testing of Caesalpinia bonducella, against H. diminuta and S. obvelata, also observed a dosedependent efficacy of extract [18].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…To date, only a few studies on anthelmintic potentials of medicinal plants have backed their in vitro assays with in vivo studies. For example, Gogoi and Yadav (2016) and Gogoi and Yadav (2017) have supplemented their in vitro anthelmintic studies of plants with in vivo studies, using H. diminuta-rat and S. obvelata-mice models [18,30]. The findings are in agreement with that of Gogoi and Yadav (2016), who in their in vitro and in vivo efficacy testing of Caesalpinia bonducella, against H. diminuta and S. obvelata, also observed a dosedependent efficacy of extract [18].…”
Section: Discussionsupporting
confidence: 53%
“…In another study by Gogoi and Yadav (2017), the in vitro and in vivo anthelmintic efficacy of Croton joufra leaf extract was investigated against H. diminuta. The in vitro study showed a dose-dependent effect on parasite, and the highest concentration of the extract (30 mg/ml) caused mortality of in worms 1.53 ± 0.12 h, p<0.001 as compared to control value, b p<0.001 as compared to pre-treatment period, one-way ANOVA, followed by Tukey's test compared to 3.46 ± 0.10 h shown by PZQ (1 mg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Protoberberines are another class of tetracyclic benzylisoquinolines that display antagonism at Sm.5HTR L . Rotundine is a constituent of traditional Chinese herbal medicine preparations, with activity against both cestodes (Das et al, 2009; Gogoi and Yadav, 2017) and schistosomes (Chan et al, 2016c). We previously identified racemic D/L-rotundine) as an antagonist at Sm.5HTR L and showed this compound inhibited movement of adult worms (Chan et al, 2016c).…”
Section: Resultsmentioning
confidence: 99%
“…The successful functional expression and miniaturization of a Sm.5HTR L profiling assay has enabled high-throughput compound screens to identify ligands with potential anti-schistosomal activity (Chan et al, 2018). Given these data validating Sm.5HTR L as a viable anti-schistosomal drug target, and the precedent of both tryptaminergic and benzylisoquinoline natural products as serotonergic ligands (Cabedo et al, 2009; Nichols, 2012; Harding, 2016) and antiparasitic compounds (Bonne, 1919; Iwasa et al, 1999; Nkwengoua et al, 2009; Das et al, 2009; Shahinas et al, 2012; Gogoi and Yadav, 2017), we performed a more detailed exploration of the properties of these pharmacophores that determine their efficacy as Sm.5HTR L ligands and activity against ex vivo cultured parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Although the usage of traditional medicine has increased worldwide, research in this area is inadequate [6]. Several authors have scientifically validated the efficacy of plants used in traditional medicines to treat helminthiasis through both in vitro and in vivo studies and have found them to be efficacious [7,8].…”
Section: Introductionmentioning
confidence: 99%